2011
DOI: 10.1016/j.jtcvs.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of acute type B aortic dissection: Ulcer-like projections in thrombosed false lumen play a role in late aortic events

Abstract: In type B aortic dissection, a thrombosed false lumen with ulcer-like projections and a patent false lumen had an influence on late aortic dilation and late aortic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Subgroup analysis showed that the pooled HR for long‐term mortality with postoperative residual patent false lumen was 2.02 (95% CI, 1.13–3.61; P =0.017) with no significant heterogeneity (I 2 =29.6%; P =0.233). For studies in the type B category,18, 19, 28 the pooled HR for long‐term mortality with preoperative residual patent false lumen was 2.79 (95% CI, 1.80–4.32; P <0.001; Figure 2); no statistically significant heterogeneity was observed (I 2 =0.0%; P =0.386). Because of the small number of studies, sensitivity analysis and Egger's test were not performed.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Subgroup analysis showed that the pooled HR for long‐term mortality with postoperative residual patent false lumen was 2.02 (95% CI, 1.13–3.61; P =0.017) with no significant heterogeneity (I 2 =29.6%; P =0.233). For studies in the type B category,18, 19, 28 the pooled HR for long‐term mortality with preoperative residual patent false lumen was 2.79 (95% CI, 1.80–4.32; P <0.001; Figure 2); no statistically significant heterogeneity was observed (I 2 =0.0%; P =0.386). Because of the small number of studies, sensitivity analysis and Egger's test were not performed.…”
Section: Resultsmentioning
confidence: 96%
“…Four studies17, 22, 26, 27 examined the association between the false lumen status and AAD outcomes in type A patients, and another 6 studies18, 19, 20, 28, 29, 30 examined associations in type B patients. One study21 included both type A (73%) and type B (27%) AAD; in subgroup analysis based on the Stanford classification, this study was placed in the type A group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 However these studies have shown that aortic diameter >40 mm correlates with aortic growth. 10,19,[22][23][24][25][26][27] The current study shows that an aortic diameter >35 mm is a risk factor for subsequent aortic dilation. In future trials of TEVAR for acute type B dissection, this lower threshold should be considered.…”
Section: Discussionmentioning
confidence: 48%